2000
DOI: 10.1023/a:1007691003600
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A number of epidemiological studies have addressed the risk of pleural mesothelioma from environmental (household and neighborhood) exposure to asbestos, but no overall risk estimate is available. We reviewed the epidemiological studies on risk of pleural mesothelioma and household or neighborhood exposure to asbestos. We identified eight relevant studies; most were conducted in populations with relatively high exposure levels. We combined the risk estimates in a meta-analysis based on the random-effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The importance of non-occupational, domestic or environmental (neighbourhood) asbestos exposure has been underlined in many reports (Bourdes et al 2000;Boffetta 2006;Pasetto et al 2005;Magnani et al 2000;Magnani et al 2001;Maule et al 2007). Our study is a further contribution to explain the asbestos drama in the city of Bari, the presence of the AC factory has been related with the onset of malignant mesothelioma among the neighboring resident population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of non-occupational, domestic or environmental (neighbourhood) asbestos exposure has been underlined in many reports (Bourdes et al 2000;Boffetta 2006;Pasetto et al 2005;Magnani et al 2000;Magnani et al 2001;Maule et al 2007). Our study is a further contribution to explain the asbestos drama in the city of Bari, the presence of the AC factory has been related with the onset of malignant mesothelioma among the neighboring resident population.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated an increased risk, even in the general population, associated with relatively low asbestos exposure of environmental type (Bourdes et al 2000;Boffetta 2006). The environmental pollution was reported to be derived from industrial sites or mines, from the presence of asbestos in buildings (asbestos in place), but also from natural contamination of the soil, in which case exposure can date right from birth ).…”
Section: Introductionmentioning
confidence: 99%
“…If short exposures can lead to MPM, the tumor is mostly the consequence of long-time exposure [63, 64]. Although asbestos exposure can be environmental [65,66,67], most cases result from occupational exposures. That is the reason why the incidence of MPM shows marked differences between countries [68].…”
Section: Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…For neighborhood exposure, RRs ranged between 5.1 and 9.3 (with a single RR of 0.2) and the summary estimate was 7.0 (95% CI 4.7-11). These results indicate an increased risk of pleura mesothelioma from high environmental asbestos exposure; although, the data was unable to offer the magnitude of the excess risk at levels which correspond to environmental exposure to the general population in industrial countries (Bourdès et al, 2000).…”
Section: Mesotheliomamentioning
confidence: 74%
“…The RRs of pleural mesothelioma for household exposure ranged from 4.0 to 23.7 and the summary risk estimate was 8.1 (95% CI 5.3-12) (Bourdès et al, 2000). For neighborhood exposure, RRs ranged between 5.1 and 9.3 (with a single RR of 0.2) and the summary estimate was 7.0 (95% CI 4.7-11).…”
Section: Mesotheliomamentioning
confidence: 96%